HW3 Solutions

HW3 Solutions - Math 131A Analysis Summer Session A...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 131A Analysis Summer Session A Homework 3 Solutions 1. Let ( a n ) be a bounded sequence and let ( b n ) be a sequence such that lim n b n = 0. Prove that lim n a n b n = 0. Proof. Since ( a n ) is bounded, there exists M > 0 such that | a n | < M for all n N . For all n N , we have | a n b n | = | a n || b n | < M | b n | , or equivalently,- M | b n | < a n b n < M | b n | . Since b n 0, we have | b n | 0 by the limit theorems. Thus M | b n | 0 by the limit theorems. By the Squeeze Theorem, a n b n 0. 2. Let p > 0 be a positive real number. Then prove lim n a n n p = if | a | 1 + if a > 1 does not exist if a <- 1 Proof. If | a | 1, the sequence a n is bounded. Indeed, | a n | = | a | n 1 for all n N . Also 1 n p 0 for all p > 0. Thus by Problem 1, lim n a n n p = 0. If a > 1, then by the limit theorems, we have a n +1 ( n +1) p a n n p = a n +1 a n n p ( n + 1) p = a n n + 1 p = a 1 1 + 1 n p a > 1 Thus by Homework 2, problem 7b, we have lim n a n n p = lim n a n n p = . If a <- 1, then to show the limit does not exist, it suffices to prove lim n a 2 n (2 n ) p = and lim n a 2 n- 1 (2 n- 1) p =- since that implies liminf a n n p =- < = limsup a n n p Since a 2( n +1)- 1 (2( n +1)- 1) p a 2 n- 1 (2 n- 1) p = a 2 n +1 (2 n +1) p a 2 n- 1 (2 n- 1) p = a 2 2 n- 1 2 n + 1 p a 2 > 1 1 by Homework 2, problem 7b we have lim n a 2 n- 1 (2 n- 1) p = lim n - a 2 n- 1 (2 n- 1) p = + Thus lim n a 2 n- 1 (2 n- 1) p =- Similarly, a 2( n +1) (2( n +1)) p a 2 n (2 n ) p = a 2 n +2 (2 n +2) p a 2 n (2 n ) p = a 2 2 n + 2 2 n p a 2 > 1 by Homework 2, problem 7b we have lim n a 2 n (2 n ) p = lim n a 2 n (2 n ) p = + 3. If lim n s n = + and k < 0, prove lim n ks n =- . Proof. Define a sequence k n = k for all n N . Clearly, k n k < 0. Thus- k n - k > 0. By Theorem 9 . 9, lim n - s n k n = lim n s n (- k n ) = + , which implies lim n ks n = lim n - (- s n k n ) =- . 4. If lim n s n = + and ( t n ) is a bounded sequence, prove lim n s n + t n = + . Proof. Since ( t n ) is bounded, there exists C > 0 such that- C < t n < C for all n N . Let M > 0. Since lim n s n = + , there exists N N so that s n > M + C for all n > N . Thus s n + t n > ( M + C )- C = M for all n > N ....
View Full Document

Page1 / 9

HW3 Solutions - Math 131A Analysis Summer Session A...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online